Investigating the factors affecting the PISA-based test performance of Asian students - Çağlayan Akay, Ebru; Oskonbaeva, Zamira (Economic Journal of Emerging Markets, 2024)
Purpose ― This study investigates the factors affecting the learning outcomes of Asian students. Methods ─ The effects of both educational inputs and economic and socioeconomic variables on the PISA scores of 10 Asian countries (Hong Kong, Indonesia, Japan, Singapore, Macau, Korea, Turkey, Israel, Qatar, and Thailand) for the years 2006, 2009, 2012 and 2015 were examined using unbalanced panel data. Findings ─ The results show that country-level economic factors strongly affect academic achievement. Furthermore, country-level economic factors dominate the other explanatory factors in the numerical and statistical sense. Implication ─ The findings provide valuable information for educators, policymakers, and researchers aiming to develop efficient educational strategies to improve educational quality. Furthermore, the results offer policy suggestions for addressing factors that impact the quality of education both at the national and international levels.Originality ─ This research enhances the current body of knowledge by investigating how economic and socioeconomic variables affect students' math, science, and reading performance, particularly emphasizing Asian countries.